Structural Dynamics of Employment of Older People in the Eurasian Economic Union Countries - Kalabina, Elena G.; Gazizova, Maiya R.; Khussainova, Zhibek S. (Economy of Regions, 2021)
Employment of older people can help solve problems arising from the population ageing. The growing demand for such employees creates favourable conditions for the realisation of their resource potential. In order to identify potential sectors for the employment of older workers, the study assesses structural shifts in the labour market by type of economic activity in the Eurasian Economic Union (EAEU). It was hypothesised that, despite labour potential differences, the EAEU countries have similar industries characterised by positive trends toward increasing employment of older workers. After identifying these trends, the research classified theoretical approaches to the study of employment opportunities for older adults. The assessment of structural differences in employment by type of economic activity was conducted based on the selected methodology. To quantify changes in the EAEU countries, employment of older workers was analysed using the integral coefficients of structural shifts of Gatev and Ryabtsev. According to statistics on the population employment for 2014-2019, older people of the EAEU countries (except Armenia) can continue to work in real estate transactions, hotels and public catering establishments, as well as in the field of health care and social services. To stimulate the employment of older workers in these areas, state measures, based on the proposed recommendations, can focus on promoting entrepreneurship and expanding the information environment for older people.